The Telegraph Equation and Its Solution by Reduced Differential Transform Method. (15th September 2013) - Srivastava, Vineet K.; Awasthi, Mukesh K.; Chaurasia, R. K.; Tamsir, M.
Abstract : One-dimensional second-order hyperbolic telegraph equation was formulated using Ohm's law and solved by a recent and reliable semianalytic method, namely, the reduced differential transform method (RDTM). Using this method, it is possible to find the exact solution or a closed approximate solution of a differential equation. Three numerical examples have been carried out in order to check the effectiveness, the accuracy, and convergence of the method. The RDTM is a powerful mathematical technique for solving wide range of problems arising in science and engineering fields.